Islamic Religious Education Model Based on National Values to Improve Interfaith Tolerance - Istighosah (International Journal of Islamic Education Studies, 2025)
Low motivation among students in learning Islamic Religious Education (PAI) remains a challenge in secondary schools, affecting both engagement and the internalization of moral and religious values. This study aims to explore the role of teachers in enhancing students’ motivation in PAI at SMA Islam Al Fattah Pungpungan, identifying effective strategies, relational practices, and classroom dynamics that influence learning motivation. A qualitative case study approach was employed, involving classroom observations, semi-structured interviews with teachers and students, and document analysis of lesson plans and teaching materials. Data were analyzed thematically to uncover patterns and insights regarding teacher practices and their impact on student motivation. The findings reveal that teachers significantly influence students’ motivation through contextualized lessons, interactive and collaborative learning activities, personalized feedback, and the integration of multimedia resources. Positive teacher-student relationships, characterized by empathy, trust, and supportive communication, further enhance intrinsic motivation and encourage active participation in class. Challenges such as varying student interest, external distractions, and sensitive topics were observed, yet teachers who demonstrated creativity, adaptability, and commitment successfully maintained a motivating and engaging learning environment.